Vibration Characteristics of Engine Support Bracket Using Finite Element Analysis - Kamarul Zaman, Muhammad Akmalhakim; Subramaniyan, S Kanna (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Engine support bracket play a vital role of reducing the noise, vibration, and harshness. Engine support bracket is important part of the Engine mount that have function to absorbing the vibration of the car engine and hinder this vibration from going into car passenger. Vibration is producing the natural frequency of the moving part and the speed of the car that produce by car engine. The higher speed of car will provide more vibration. In order to reduce the natural frequency of the engine support bracket, the Finite Element Analysis (FEA) has been done using the Abaqus software. The objective of this research is to investigate about the natural frequency of the car engine support bracket. Also, another objective is to modify the engine support bracket by doing design optimization and comparing the design frequency with the previous study. Based on these two objectives, the model of engine support bracket has been modified from the previous study model using the design optimization method by SolidWork 2019 software. The new part has been adding in the engine support bracket to make the differences between previous study models. The dimension of the addition part is rectangular par that have length 200 mm, width 20 mm and the thickness 10 mm. For the natural frequency and its deformation, Abaqus 2017 Software was using for the simulation test. The research has provided the natural frequency and deformation for the engine support bracket model for two materials which is Magnesium Alloy and ERW-1 material. ERW-1 material is the material that commonly use in the automation industries. This simulation produce the frequency result and it also has reducing the frequency for the ERW-1 material from the previous study. The simulation has shown the ERW-1 material is suitable material for the modified model of the engine support bracket. The vibration of the engine support bracket has been reduced because the natural frequency was reduced. To conclude, this simulation is likely to succeed and can be carried forward to further simulation for better improvement.